2021
DOI: 10.1111/jar.12878
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and people with intellectual disabilities: A systematic review

Abstract: Social networks can be defined as 'opportunity structures' (Forrester-Jones and Grant, 1997, p. 7) or interpersonal relationships (Sullivan et al., 2016). Social networks can contain a range of people, including partners, family, friends, acquaintances, professionals and neighbours. Hill and Dunbar (2003) reported typical network size for nondisabled adults as over 100 contacts dispersed across different areas of life. Social network size for adults with intellectual disabilities however is smaller and more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
0
19
0
2
Order By: Relevance
“…Mithen et al (2015) measured social capital across informal and formal networks and found that individuals with intellectual disability were worse off than those with other disabilities or without disabilities with regard to the social support they received from their networks. Harrison et al (2021) reported that the networks of persons with intellectual disability were significantly smaller and less diverse than those of non-disabled persons, which could influence the amount of support and resources available to them. This is in line with results from Hindmarsh et al (2015), who reported that parents had less social support and were less likely to have other parents to talk to and someone to share their feelings with compared with a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Mithen et al (2015) measured social capital across informal and formal networks and found that individuals with intellectual disability were worse off than those with other disabilities or without disabilities with regard to the social support they received from their networks. Harrison et al (2021) reported that the networks of persons with intellectual disability were significantly smaller and less diverse than those of non-disabled persons, which could influence the amount of support and resources available to them. This is in line with results from Hindmarsh et al (2015), who reported that parents had less social support and were less likely to have other parents to talk to and someone to share their feelings with compared with a control group.…”
Section: Introductionmentioning
confidence: 99%
“…However, online social connections were not straightforward or easily accessible for everyone. It is known that people with learning disabilities often have reduced social networks (Harrison et al, 2021) and during the early stages of the Covid-19 pandemic, social isolation was identified as a worry for people with learning disabilities . Responses were entered directly into the Qualtrics™ online survey by respondents.…”
Section: The Covid-19 Pandemicmentioning
confidence: 99%
“…Continuing along the path of the justifications for community inclusion, a secondary outcome can be increased opportunities for expanding social networks and building social relationships with others. Social networks are a web of relationships connected to an individual, strengthened by the quality and quantity of relationships within the said network and have been noted to mediate social functioning, self-esteem and quality of life (Forrester-Jones et al , 2004; Harrison et al , 2021). Chithrangathan (2022) provide an interesting and uplifting finding of increased fraternity, cooperation and altruism in students, with students being reported to have frequently helped other students complete vocational tasks, as reported by teachers and parents.…”
Section: Social Inclusion Through Vocationmentioning
confidence: 99%